2021
DOI: 10.3390/w13111527
|View full text |Cite
|
Sign up to set email alerts
|

Treated Wastewater Irrigation—A Review

Abstract: As the most important resource for life, water has been a central issue on the international agenda for several decades. Yet, the world’s supply of clean freshwater is steadily decreasing due to extensive agricultural demand for irrigated lands. Therefore, water resources should be used with greater efficiency, and the use of non-traditional water resources, such as Treated Wastewater (TW), should be increased. Reusing TW could be an alternative option to increase water resources. Thus, many countries have dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 269 publications
0
71
1
4
Order By: Relevance
“…However, the AF effluent proved to be unfit for maize production with regards to contribution to N and P uptake. This is contrary to reports given by some authors [30,31] that treated wastewater can supply nutrients to increase crop yields, which is not always the case. Overapplication of nutrients such as N is likely to cause delayed flowering and uneven ripening.…”
Section: Contribution To N and P Removalcontrasting
confidence: 96%
“…However, the AF effluent proved to be unfit for maize production with regards to contribution to N and P uptake. This is contrary to reports given by some authors [30,31] that treated wastewater can supply nutrients to increase crop yields, which is not always the case. Overapplication of nutrients such as N is likely to cause delayed flowering and uneven ripening.…”
Section: Contribution To N and P Removalcontrasting
confidence: 96%
“…It activates various enzymes involved in the metabolism of plants. Studies have shown that in soils that receive TWW for irrigation, the availability of total N, K, and available P increase considerably [52][53][54][55][56]. Similarly, Abd-Elwahed [57] and Xu et al [58] observed increased total N, available K, and P contents in the top layer of soil for irrigated plants with wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the continuous availability of essential nutrients present in TWW enhanced total chlorophyll, photosynthesis rate, and plant growth, which then results in higher maximum leaf area, plant height, and total biomass. TTW also contains the trace-elements (Mn, Zn, Fe, and Cu) and organic matter necessary for plant growth [56,59]. This makes TTW rich in fertilizers that can increase the fertility of soil and enhance crop yield [60][61][62], since trace-elements have critical importance and play significant roles in plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations